Public Knowledge about Covid-19 and Public Behavior During the Covid-19 Pandemic - Yanti, Ni Putu Emy Darma; Nugraha, I Made Arie Dharma Putra; Wisnawa, Gede Adi; Agustina, Ni Putu Dian; Diantari, Ni Putu Arsita (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Coronavirus 2019 or COVID-19 is a pandemic that has resulted in mortality and mortality rates in various parts of the world. Good knowledge of the COVID-19 pandemic and having a clean and healthy behavior as an effort to prevent transmission of COVID-19 is important to apply. The aim of the research is to find a picture of the community about the COVID-19 pandemic and people's behavior during the COVID-19 pandemic. This type of research is quantitative with a descriptive survey design on 150 communities in Sumerta Kelod Village, Denpasar, Bali through purposive sampling. Research using a questionnaire as a data tool and the data were analyzed univariately by presenting the variable frequency distribution. The results of the analysis obtained public knowledge about the COVID-19 pandemic in the good category, namely 70%. The distribution of community behavior shows that the community has complied with health protocols during the COVID-19 pandemic. Most of the community case categories are in the low-risk case category (85.33%).